2018
DOI: 10.1016/j.arth.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Managing Prolonged Pain After Surgery: Examining the Role of Opioids

Abstract: A notable minority of patients experience persistent postsurgical pain and some of these patients consequently have prolonged exposure to opioids. Risk factors for prolonged opioid use after surgery include preoperative opioid use, anxiety, substance abuse, and alcohol abuse. The window to intervene and potentially prevent persistent opioid use after surgery is short and may best be accomplished by both surgeon and anesthesiologist working together. Anesthesiologists in particular are well positioned in the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Persistent pain may also lead to the increased consumption of analgesics [8]. To date, however, only a limited number of large-scale studies have been conducted on the trajectories of analgesic consumption and the risk factors associated with increased analgesic consumption after surgery [9][10][11][12][13][14][15][16][17][18][19][20][21], even though the risks for adverse events of opioids and non-steroidal anti-inflammatory drugs increase in long-term use [22][23][24], especially in elderly patients with comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent pain may also lead to the increased consumption of analgesics [8]. To date, however, only a limited number of large-scale studies have been conducted on the trajectories of analgesic consumption and the risk factors associated with increased analgesic consumption after surgery [9][10][11][12][13][14][15][16][17][18][19][20][21], even though the risks for adverse events of opioids and non-steroidal anti-inflammatory drugs increase in long-term use [22][23][24], especially in elderly patients with comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Although a 10 mg or 25-30% intravenous opioid difference is considered clinically significant in most studies on postoperative analgesia. However, most of those studies [2,3] were conducted to compare between a placebos or single intervention group with a multiple intervention group, contrary to our study which is an active comparison between multiple peripheral nerve blocks combined with multimodal analgesia. Therefore, the drastic differences in postoperative analgesia and opioid consumption, albeit statistically significant, were not observed between the groups.…”
Section: In Replymentioning
confidence: 82%
“…An ideal postoperative analgesic regimen should incorporate specific medications to address all the components of pain (e.g., neuropathic, inflammatory). The physician should consider if opioids are even needed and, if so, the optimal prescription . A multimodal analgesic approach is often recommended and has been shown to reduce opioid consumption in surgical patients .…”
Section: Guidancementioning
confidence: 99%
“…Non‐opioid medications, such as acetaminophen or ibuprofen, should first be encouraged for pain treatment, as should non‐ pharmacologic options, including ice, elevation, physical therapy, electrotherapy, and acupuncture . Peripheral nerve blocks and neuraxial analgesia are other options to reduce opioid use while still reaching recovery objectives . Prochazka indicated that assessing patient pain and respiratory status also is vital in the postoperative period.…”
Section: Guidancementioning
confidence: 99%
See 1 more Smart Citation